DA-MIL-101 (Fe) nano material and on-off ratio electrochemical sensor
By using DA-MIL-101(Fe) nanomaterials to construct an on-off ratio electrochemical sensor, the problem of poor analytical accuracy and reproducibility of traditional electrochemical detection technology in complex environments is solved, and the detection of multiple metal ions is achieved. High sensitivity and stability detection.
Patent Information
- Application Number
- CN202411362540.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional electrochemical detection technology is susceptible to interference from instrument parameters, electrode modification process and analysis conditions in metal ion analysis, resulting in poor accuracy and reproducibility of analysis results, especially in complex environments that are difficult to effectively detect.
DA-MIL-101(Fe) nanomaterial is used to construct an on-off ratio electrochemical sensor. Dual independent electrochemical signals are formed through chemical grafting of DA and MIL-101(Fe). The on-off ratio sensing mode is used to overcome errors and Environmental impact, improve the reproducibility and reliability of detection.
It achieves highly sensitive detection of multiple metal ions in different valence states, especially the qualitative and quantitative analysis of Pb2+, improves the stability and anti-interference ability of electrochemical detection, and has a specific recognition mechanism.
Smart Images

Figure CN119331256A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical detection, and in particular relates to a DA-MIL-101 (Fe) nano material and an on-off ratio electrochemical sensor. Background Art
[0002] Metal ions, especially heavy metal ions, are common sources of pollution in environmental water, which may pose a serious threat to human health and are considered to be the initiators of various diseases. In recent decades, electrochemical technology has attracted widespread attention in metal ion sensing due to its advantages of high sensitivity, low cost, easy operation and fast response speed. Traditionally, the electrochemical detection of metal ions is based on the anodic stripping voltammetry (ASV) technique, which includes two main steps: preconcentration (electrodeposition) and stripping (reoxidation). The current response generated during the stripping process is proportional to the initial concentration of metal ions in the solution. It can be found that in the traditional sensing mode, the successful analysis of metal ions relies on their single signal. Undoubtedly, it is easily interfered by various analyte-independent factors, such as instrument parameters, electrode modification process, analytical conditions, etc. This usually leads to poor accuracy and reproducibility of the analytical results, limiting the practical application of electrochemical sensors in metal ion sensing, especially in complex environments.
[0003] Recently, the ratiometric electrochemical technique of dual-signal mode has attracted more and more interest. By introducing dual independent signals, the target substance can be analyzed by the relationship between the ratio signal and the concentration of the target substance. Obviously, the ratiometric electrochemical technique can overcome unexpected errors and environmental influences and improve the reproducibility and reliability of electrochemical detection. In general, the implementation of dual-signal mode is based on two types: signal on / off and signal on-off. The former represents a stable signal while the other varies with the analyte; the latter depends on two signals that vary with the analyte, and the analyte usually shows signals in opposite ways. For the analysis of metal ions, most reports are based on the on / off ratiometric mode, introducing a stable reference probe such as bismuth particles, methylene blue, ferrocene, and thiophene. In general, the on-off ratiometric sensor has greater advantages than the on / off ratiometric mode in the electrochemical detection of metal ions, but it is more difficult. Therefore, it is of great significance to develop an on-off ratiometric electrochemical sensor that can directly detect metal ions. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a DA-MIL-101 (Fe) nanomaterial and an on-off ratio electrochemical sensor. The DA-MIL-101 (Fe) nanomaterial includes MIL-101 (Fe) and DA (dopamine) chemically grafted on the surface of MIL-101 (Fe). After using it to construct an electrochemical sensor, it can provide two independent electrochemical signals on the surface of the sensor, significantly enhancing the sensitivity, stability and reliability of the sensor.
[0005] The invention provides a DA-MIL-101 (Fe) nano material, which comprises DA and MIL-101 (Fe), and DA is chemically grafted on the surface of MIL-101 (Fe).
[0006] In the present invention, when the DA-MIL-101 (Fe) nanomaterial is used in an electrochemical sensor to detect metal ions, two separate electrochemical signals for detecting metal ions are provided: one is an important signal from DA, which serves as an internal reference, and the other is from the corresponding metal ions; as the concentration of metal ions increases, the signal of the metal ions increases, while the signal of DA decreases, which causes the interaction between DA and the metal ions, affecting the oxidation of hydroxyl groups in DA to quinones, thereby forming a switching ratio strategy, overcoming the influence of errors and the environment, and improving the reproducibility and reliability of electrochemical detection.
[0007] Preferably, the mass ratio of DA to MIL-101(Fe) is 3-8:1.
[0008] Preferably, the particle size of the MIL-101(Fe) is 200-300 nm.
[0009] The present invention also proposes a method for preparing a DA-MIL-101 (Fe) nanomaterial, which comprises: chemically grafting DA onto the surface of MIL-101 (Fe) through an amidation reaction, thereby obtaining the DA-MIL-101 (Fe) nanomaterial.
[0010] Preferably, the amidation reaction uses EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride) / NHS (N-hydroxysuccinimide) reagent as a catalyst.
[0011] Preferably, the MIL-101(Fe) is obtained by mixing FeCl3, PTA (terephthalic acid), water and DMF (N,N-dimethylformamide) and heating the mixture.
[0012] Preferably, the heating reaction temperature is 60-70°C.
[0013] Preferably, the preparation method specifically comprises: adding MIL-101(Fe) to ethanol and dispersing it evenly, then adding EDC and NHS, and then adding DA, stirring and reacting at 10-30°C for 5-20h to obtain the DA-MIL-101(Fe) nanomaterial.
[0014] Preferably, the particle size of the DA-MIL-101(Fe) nanomaterial is 300-350 nm.
[0015] The present invention also provides an on-off ratio electrochemical sensor, which comprises the above-mentioned DA-MIL-101 (Fe) nanomaterial or the DA-MIL-101 (Fe) nanomaterial prepared by the above-mentioned preparation method.
[0016] Preferably, the DA-MIL-101(Fe) nanomaterial is used as a working electrode after being used to modify GCE.
[0017] Preferably, the on-off ratio electrochemical sensor is used for analytical detection of metal ions in solution.
[0018] Beneficial technical effects:
[0019] (1) In the DA-MIL-101(Fe) nanomaterial of the present invention, due to the specific chemical bridging relationship between DA and MIL-101(Fe), the DA-MIL-101(Fe) nanomaterial formed by the composite of the two can generate dual independent electrochemical signals after being used to construct an electrochemical sensor, which is used to detect multiple metal ions of different valence states, especially Pb 2+ As a representative target, Pb 2+ As the metal ion binds to DA-MIL-101 (Fe), the electrochemical response of DA decreases with the increase of metal ion concentration. 2+ The electrochemical response of the sensor increases accordingly, thus establishing a switch ratio sensing mode. Pb 2+ / I DA , with I Pb 2+ / I DA The signal is output, and the DA-MIL-101(Fe) nanomaterial shows I Pb 2+ / I DA Concentration and Pb 2+ There is a good linear relationship between the concentrations of Pb 2+ It is possible to perform qualitative and quantitative analysis, indicating that the electrochemical sensor constructed with DA-MIL-101(Fe) has high stability and good anti-interference ability.
[0020] (2) In the present invention, the phenolic hydroxyl group of DA can serve as a binding site for metal ions and can form a metal-oxygen bond. + 、Cd 2+ , Cu 2+ , Pb 2+ 、Bi 3+ 、In 3+ ) has different binding abilities with DA at different valence states, and the calculated binding energy reveals the specific recognition mechanism of DA phenolic hydroxyl group and different metal ions. Therefore, the DA-MIL-101(Fe) nanomaterial can show different electrochemical properties for different metal ions at different valence states, and the electrochemical sensor constructed by it can have a specific recognition mechanism for metal ions with the same valence state but different types or the same type but different valence states.
[0021] (3) In the present invention, the DA-MIL-101(Fe) nanomaterial has an electrochemical performance preference for specific divalent metal ions compared to trivalent metal ions, indicating that the binding strength of DA with metal ions and the catalytic activity of MIL-101(Fe) have a synergistic effect. It can be seen that the on-off ratio electrochemical sensor constructed based on the DA-MIL-101(Fe) nanomaterial can be used as a reliable and sensitive ratio platform for metal ion detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation process of DA-MIL-101(Fe) in Example 1 of the present invention;
[0023] Figure 2 The SEM images of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention are as follows: (a) is the SEM image of MIL-101(Fe), and (b) is the SEM image of DA-MIL-101(Fe);
[0024] Figure 3 XRD patterns of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention;
[0025] Figure 4 FTIR spectra of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention;
[0026] Figure 5The XPS characterization diagrams of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention are as follows: (a) is the XPS characterization diagram of MIL-101(Fe), DA-MIL-101(Fe), DA-MIL-101(Fe) and Pb 2+ Complex Pb 2+ -XPS spectrum of DA-MIL-101(Fe); (b) is the XPS spectrum of DA-MIL-101(Fe) and Pb 2+ Complex Pb 2+ -High-resolution XPS spectrum of Pb 4f of DA-MIL-101(Fe); (c) High-resolution XPS spectrum of O1s of DA-MIL-101(Fe); (d) 2+ Complex Pb 2+ -High-resolution XPS spectrum of O1s of DA-MIL-101(Fe);
[0027] Figure 6 The DA-MIL-101(Fe) to Pb in Example 1 of the present invention 2+ Electrochemical test diagram: (a) DA-MIL-101(Fe) to different concentrations of Pb 2+ SWV curve of I Pb 2+ / I DA With Pb 2+ (c) is the enlarged diagram of the DA signal change in (a); (d) is the corresponding calibration diagram of I DA Pb 2+ concentration dependence plot;
[0028] Figure 7 The MIL-101 (Fe) to Pb in Comparative Example 1 of the present invention is 2+ Electrochemical test diagram of MIL-101(Fe) for different concentrations of Pb 2+ SWV curve of I Pb 2+ / I DA With Pb 2+ Corresponding calibration plots between concentrations;
[0029] Figure 8 The DA-MIL-101 (Fe) to Ag in Example 1 of the present invention is + 、Cd 2+ , Cu 2+ 、Bi 3+ andIn 3+ Electrochemical test diagram: (a) DA-MIL-101(Fe) to different concentrations of Ag +SWV curve and IDA for Ag + (b) is the dependence of DA-MIL-101(Fe) on different concentrations of Cd 2+ SWV curve and IDA to Cd 2+ (c) is the dependence of DA-MIL-101(Fe) on different concentrations of Cu 2+ SWV curve and IDA of Cu 2+ (d) DA-MIL-101 to different concentrations of Bi 3+ SWV curve and IDA for Bi 3+ (e) is the dependence of DA-MIL-101(Fe) on different concentrations of In 3+ SWV curve and IDA to In 3+ Concentration dependence diagram; (f) is Ag + 、Cd 2+ , Cu 2+ , Pb 2+ 、Bi 3+ andIn 3+ Heat map of metal ion ΔI / Conc. under DA-MIL-101(Fe). DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described in detail below through specific embodiments, but the aforementioned invention content and technical solution are not limited.
[0031] Example 1
[0032] Reference Figure 1 This embodiment provides a DA-MIL-101 (Fe) nanomaterial, and its preparation method includes the following steps:
[0033] (1) 0.22 g FeCl3·6H2O was dissolved in 20 mL water to form solution 1; 0.13 g PTA was dissolved in 20 mL DMF to form solution 2; a mixed solvent containing 1.7 mL water and 3.3 mL DMF was heated to 65°C, 1 mL solution 1 and solution 2 were first injected into the mixed solvent at a rate of 0.12 mL / min using a dual-channel syringe pump, and then the remaining solution 1 and solution 2 were injected into the mixed solvent at a rate of 0.25 mL / min, and after the reaction was stirred at the temperature, the product was collected by centrifugation, and the obtained product was washed with ethanol and DMF respectively, and dried in a vacuum oven at 60°C for 10 h to obtain MIL-101 (Fe) nanoparticles;
[0034] (2) 20 mg of the MIL-101 (Fe) nanoparticles prepared above were added to 20 mL of ethanol and ultrasonically dispersed uniformly. Then, 50 mg of NHS and 50 mg of EDC were added. After ultrasonic treatment for 1.0 h, the carboxyl functional groups of MIL-101 (Fe) were activated. Then, 10 mL of 10 mg / mL DA aqueous solution was dropped under stirring conditions. The resulting mixture solution was stirred and reacted at room temperature for 10 h. The resulting product was centrifuged with ethanol and dried in a vacuum oven at 60° C. for 5 h to obtain the DA-MIL-101 (Fe) nanomaterial, which was recorded as DA-MIL-101 (Fe).
[0035] Comparative Example 1
[0036] This comparative example proposes a MIL-101 (Fe) nanomaterial, and its preparation method comprises the following steps:
[0037] 0.22 g FeCl3·6H2O was dissolved in 20 mL water to form solution 1; 0.13 g PTA (terephthalic acid) was dissolved in 20 mL DMF to form solution 2; a mixed solvent containing 1.7 mL water and 3.3 mL DMF was heated to 65° C., 1 mL solution 1 and solution 2 were first injected into the mixed solvent at a rate of 0.12 mL / min using a dual-channel syringe pump, and then the remaining solution 1 and solution 2 were injected into the mixed solvent at a rate of 0.25 mL / min. After the reaction was stirred at the temperature, the product was collected by centrifugation, and the obtained product was washed with ethanol and DMF respectively, and dried in a vacuum oven at 60° C. for 10 hours to obtain the MIL-101 (Fe) nanomaterial, which was recorded as MIL-101 (Fe).
[0038] The DA-MIL-101(Fe) obtained in Example 1 and the MIL-101(Fe) obtained in Comparative Example 1 were subjected to scanning electron microscopy, X-ray diffraction and infrared spectroscopy. The results are as follows: Figure 3-5 shown.
[0039] Figure 2 The SEM images of MIL-101(Fe) and DA-MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that MIL-101(Fe) presents an octahedral morphology of uniform size and regular shape, with a neat and smooth surface. A layer of dopamine is obviously attached to the surface of the DA-MIL-101(Fe) octahedron, and its shape is slightly blurred and the surface is rough.
[0040] Figure 3 The XRD patterns of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 3It can be seen that the XRD patterns can confirm that MIL-101(Fe) was successfully prepared, and the almost consistent patterns between MIL-101(Fe) and DA-MIL-101(Fe) indicate the maintenance of the crystal structure of MIL-101(Fe) combined with DA molecules.
[0041] Figure 4 FTIR spectra of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention. Figure 4 It can be seen that FTIR spectroscopy provides evidence for the successful interaction between DA and the carboxyl groups on the surface of MIL-101(Fe), and an amide bond is formed between the two through chemical reaction.
[0042] The square wave voltammetry (SWV) technique was used to determine the Pb 2+ Electrochemical detection was performed. Before the measurement, 4.0 mg DA-MIL-101(Fe) or MIL-101(Fe) was added to 1 mL ethanol and ultrasonically dispersed to obtain catalyst ink. 4.0 μL of catalyst ink was dropped onto the surface of fresh GCE and dried completely at room temperature to obtain DA-MA-MIL-101(Fe) modified GCE electrode or MIL-101(Fe) modified GCE electrode. 0.1 M NaAc-Hac was used as the buffer solution. After adjusting the pH to 5.0, different concentrations of Pb were added to the 0.1 M NaAc-Hac buffer solution. 2+ The concentration range of DA-MIL-101(Fe) in different Pb 2+ SWV curve under different concentrations, draw data curve and I Pb 2+ / I DA With Pb 2+ The corresponding calibration graph between the concentrations is shown in Figure 2. Figure 5 , 6 , as shown in 7.
[0043] Figure 5 The XPS characterization diagrams of DA-MIL-101(Fe) and MIL-101(Fe) in Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 5 It can be seen that the effective functionalization of MIL-101(Fe) nanoparticles with DA provides high-resolution and high-intensity evidence. In addition, with Pb 2+ After the reaction, Pb 2+ -DA-MIL-101(Fe) introduces an additional Pb peak compared to DA-MIL-101(Fe), indicating that Pb 2+ successful combination.
[0044] Figure 6 The DA-MIL-101(Fe) to Pb in Example 1 of the present invention 2+ Electrochemical test diagram, Figure 6 a is the effect of DA-MIL-101(Fe) on different concentrations of Pb 2+ SWV curve, refer to Figure 6 a It can be seen that there are two clear peaks at potential values of around -0.45V and 0.35V, corresponding to Pb 2+ and DA, and along with Pb 2+ The increase in Pb concentration 2+ The response of increased, while that of DA decreased; Figure 6 b is I Pb 2+ / I DA With Pb 2+ The corresponding calibration graph between concentrations, refer to Figure 6 bIt can be seen that I Pb 2+ / I DA Ratio and Pb 2+ The relationship between the concentrations is demonstrated by the following linear regression equation: Pb 2+ / I DA =0.637C Pb 2+ +0.372(R 2 =0.964),I Pb 2+ / I DA =5.388C Pb 2+ -8.186(R 2 =0.980); Figure 6 c and 6d are the DA currents on Pb 2+ The dependence of the increase was in the range of 0-10 μM. The enlarged view shown in ref. 6c highlights the significant changes in the DA current response. The dashed line is the absence of Pb. 2+ The limit of detection (LOD) was calculated to be 0.056 μM, which is due to the presence of Pb 2+ Combined with the hydroxyl group of DA molecules, thus inhibiting the oxidation process of DA; at low concentrations of Pb 2+ The decrease of DA response was more obvious when Pb 2+ With the increase of concentration, the DA response gradually decreased and finally reached a plateau, indicating that the binding sites on the surface of MIL-101(Fe) were close to saturation.
[0045] Figure 7 The MIL-101 (Fe) to Pb in Comparative Example 1 of the present invention is 2+ Electrochemical test diagram, refer to Figure 7It can be seen that when MIL-101(Fe) is not bridged by DA, its modified GCE electrode has a strong electrochemical activity against Pb 2+ The weak electric response potential is -0.45 V, and no double electrochemical signal is generated for Pb 2+ The current response range of DA-MIL-101(Fe) / GCE is 2.0-6.0 μM, and the calibration plot is poor. DA-MIL-101(Fe) / GCE has higher sensitivity than MIL-101(Fe) / GCE, and the limit of quantification is much lower, indicating that DA-functionalized MIL-101(Fe) is effective for Pb 2+ The detection of Pb 2+ It has a significant recognition effect, which is beneficial for Pb 2+ sensitive detection.
[0046] Square wave voltammetry (SWV) technique was used to electrochemically detect various metal ions. + 、Cd 2+ , Cu 2+ 、Bi 3+ andIn 3+ For representative monovalent, divalent and trivalent metal ions, different concentrations of Ag were prepared according to the above method before measurement. + 、Cd 2+ , Cu 2+ 、Bi 3+ andIn 3+ The electrochemical workstation was used to record the electrochemical activity of DA-MIL-101(Fe) in different Ag + 、Cd 2+ , Cu 2+ 、Bi 3+ andIn 3+ The SWV curve under the concentration is as follows Figure 8 shown.
[0047] Figure 8 The DA-MIL-101 (Fe) to Ag in Example 1 of the present invention is + 、Cd 2+ , Cu 2+ 、Bi 3+ andIn 3+ Electrochemical test diagram, Figure 8 a is Ag + , the detection range is 0-65μM; Fig. Figure 8 b is Cd 2+ , the detection range is 0-3μM; Figure 8 c is Cu 2+ , the detection range is 0-15μM; Figure 8 d is Bi 3+ , the detection range is 0-30μM; Figure 8e is In 3+ , the detection range is 0-140μM; illustrations a and b are I DA Dependence on metal ion concentration. Figure 8 It can be seen that the electrochemical performance of DA-MIL-101(Fe) / GCE for various metal ions in different oxidation states shows that the phenolic hydroxyl group of DA can serve as a binding site for metal ions and can form metal-oxygen bonds. + 、Cd 2+ , Cu 2+ , Pb 2+ 、Bi 3+ 、In 3+ are representative monovalent, divalent and trivalent metal ions, Ag + 、Cd 2+ , Cu 2 + , Pb 2+ 、Bi 3+ 、In 3+ The current response of DA-MIL-101(Fe) / GCE to Ag is generated by the reoxidation of reduced metal ions. The current response of metal ions increases with the increase of their concentration. + 、Cd 2+ , Cu 2+ , Pb 2+ 、Bi 3+ 、In 3+ The sensitivities were 0.172, 0.488, 0.019, 0.868 and 0.010 μA μM -1 It can be seen that DA-MIL-101(Fe) nanomaterials can be developed into electrochemical sensors for a variety of metal ions.
[0048] Figure 8 f is the heat map of metal ion ΔI / Conc. of different metal ions under DA-MIL-101(Fe), referring to Figure 8 It can be seen that the change of the current response of DA in the electrochemical sensing process of various metal ions is manifested as the change of DA current response (ΔI) and the metal ion concentration (C M ), where Cd 2+ and Pb 2+ During the electrochemical sensing process, significant changes in the DA current response were observed, and the response to Pb 2+ The influence of Cu 2+ and Bi 3+ In contrast, the electrochemical analysis of Ag + During the electrochemical sensing process, the change of DA current response is very small.
[0049] The present invention first synthesizes MIL-101 (Fe) nanoparticles, which use terephthalic acid, a typical organic ligand, as a linker and Fe ions as nodes. Since MIL-101 (Fe) has abundant carboxyl groups, the interaction between the amino group and the carboxyl group of the DA molecule is promoted, thereby forming a DA-MIL-101 (Fe) nanomaterial.
[0050] In the application of electrochemical detection of metal ions, after DA-MIL-101(Fe) modified GCE as the working electrode, since the metal ions can form a metal-oxygen bond with the phenolic hydroxyl group in DA, when the concentration of the measured metal ions increases, the metal ions bind to the phenolic hydroxyl group on the surface of the working electrode to generate an electrochemical signal, while the phenolic hydroxyl group not bound by the metal ions generates another electrochemical signal, Pb 2+ The electrochemical signals of Pb and DA have a clear potential gap. 2+ As the concentration increases, the DA electrochemical signal decreases, while the Pb 2+ The electrochemical signal increased accordingly, DA was used as an internal reference probe, and an on-off ratio sensing mode was established using the ratio of the electrochemical signals of metal ions and DA.
[0051] It is worth noting that the inventors found during the research that when the binding mode of DA and MIL-101(Fe) changes, such as when MIL-101(Fe) is directly immersed in a dopamine aqueous solution, the prepared nanomaterial cannot generate dual independent electrochemical signals on the sensor. This may be because in the aqueous solution, dopamine undergoes oxidative self-polymerization on MIL-101(Fe), so that the self-polymerized dopamine cannot generate sufficient chemical signals in subsequent detection.
[0052] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A DA-MIL-101 (Fe) nanomaterial, characterized in that: The nano material comprises DA and MIL-101(Fe), and DA is chemically grafted on the surface of MIL-101(Fe).
2. The DA-MIL-101 (Fe) nanomaterial according to claim 1, characterized in that: The mass ratio of the DA to the MIL-101(Fe) is 3-8:
1.
3. The DA-MIL-101 (Fe) nanomaterial according to claim 1 or 2, characterized in that: The particle size of the MIL-101(Fe) is 200-300 nm.
4. A method for preparing DA-MIL-101 (Fe) nanomaterial, characterized in that: The preparation method comprises: chemically grafting DA onto the surface of MIL-101 (Fe) through an amidation reaction, thereby obtaining the DA-MIL-101 (Fe) nanomaterial.
5. The method for preparing the DA-MIL-101 (Fe) nanomaterial according to claim 4, characterized in that: The amidation reaction uses EDC / NHS reagent as a catalyst.
6. The method for preparing the DA-MIL-101 (Fe) nanomaterial according to claim 4 or 5, characterized in that: The MIL-101(Fe) is obtained by mixing FeCl3, PTA, water and DMF and heating the mixture for reaction; Preferably, the heating reaction temperature is 60-70°C.
7. The method for preparing the DA-MIL-101 (Fe) nanomaterial according to any one of claims 4 to 6, characterized in that: The preparation method specifically comprises: adding MIL-101(Fe) into ethanol and dispersing it uniformly, then adding EDC and NHS, and then adding DA, stirring and reacting at 10-30° C. for 5-20 hours to obtain the DA-MIL-101(Fe) nanomaterial.
8. The method for preparing the DA-MIL-101 (Fe) nanomaterial according to any one of claims 4 to 7, wherein the particle size of the DA-MIL-101 (Fe) nanomaterial is 300-350 nm.
9. An on-off ratio electrochemical sensor, characterized in that: The sensor comprises the DA-MIL-101(Fe) nanomaterial according to any one of claims 1 to 3 or the DA-MIL-101(Fe) nanomaterial prepared by the preparation method according to any one of claims 4 to 8.
10. The on-off ratio electrochemical sensor according to claim 9, characterized in that: The DA-MIL-101 (Fe) nanomaterial is used to modify GCE and then serve as a working electrode; Preferably, the on-off ratio electrochemical sensor is used for analytical detection of metal ions in solution.
Citation Information
Patent Citations
Silver-gold-metal organic framework compound surface enhanced Raman scattering substrate and preparation method and application thereof
CN113667138A
Electrochemical sensor for in-situ analysis and detection of heavy metal copper ions in soil solution
CN113984861A
Broadband spectral response type antibacterial composite film as well as preparation method and application thereof
CN115463563A
Method for preparing nanohybrid used for ratiometric fluorescence and ratiometric electrochemical sensing simultaneously
US20210222063A1